1993
DOI: 10.1213/00000539-199307000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy of General Anesthesia for Cesarean Section

Abstract: To assess the adequacy of the general anesthesia commonly employed for Cesarean section, we used isolated forearm technique to study 30 parturients (physical status ASA I/II, aged 17-35 yr) scheduled for nonemergent abdominal delivery. Anesthesia was induced with intravenous thiopental (3 mg/kg, 250 mg maximum) and succinylcholine (1.5 mg/kg), and then proceeded with a mixture of 50% N2O, 50% O2, and 0.5% halothane at a flow of 5 L/min and end-tidal CO2 at 40 mm Hg. Paralysis was maintained with a 0.1% succiny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…8 Many textbooks still recommend the use of such a low dose of volatile agent (corresponding to 0.5-0.7 MAC inspired concentration) to decrease the risk for maternal awareness without inducing neonatal depression, uterine atony and increased maternal blood loss. 9;10 It is, however, important to realize that higher concentrations of volatile anesthetics could be necessary to eliminate the risk of awareness 11 and also to counteract the negative effects on uteroplacental perfusion from the maternal autonomic stress response. 12 During an EXIT procedure the ET concentration of the volatile agent is kept very high (approximately 2 MAC) in order to keep the uterus fully relaxed, provided that maternal hemodynamics and hence uteroplacental flow are not jeopardized.…”
Section: Discussionmentioning
confidence: 99%
“…8 Many textbooks still recommend the use of such a low dose of volatile agent (corresponding to 0.5-0.7 MAC inspired concentration) to decrease the risk for maternal awareness without inducing neonatal depression, uterine atony and increased maternal blood loss. 9;10 It is, however, important to realize that higher concentrations of volatile anesthetics could be necessary to eliminate the risk of awareness 11 and also to counteract the negative effects on uteroplacental perfusion from the maternal autonomic stress response. 12 During an EXIT procedure the ET concentration of the volatile agent is kept very high (approximately 2 MAC) in order to keep the uterus fully relaxed, provided that maternal hemodynamics and hence uteroplacental flow are not jeopardized.…”
Section: Discussionmentioning
confidence: 99%
“…1 Mortality related to GA was the third commonest cause of maternal deaths in England and Wales in the early 1980s, with the majority of these due to failure of intubation or pulmonary aspiration of stomach contents. 2 The judicious administration of anesthetic agents, arising from concerns of excessive neonatal sedation, also led to an increased incidence of maternal awareness under GA. 3,4 Hence, there has been a growing trend towards the use of regional anesthetic techniques such that in certain obstetric centers, general anesthesia is used only for specific indications such as severe fetal distress requiring immediate surgical delivery. 5 While regional techniques may be associated with problems such as delays in the induction of anesthesia during emergency situations, postoperative immobility secondary to residual motor weakness, urinary retention and spinal headaches, 1 its relative safety has contributed to its increased popularity.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not clear how quickly fentanyl crosses the placenta. Hence, keeping in mind the risk of fetal respiratory depression and low APGAR scores, its use was precluded in our patient before delivery of the baby [6]. Halaseh et al [7] reported that use of the Proseal laryngeal mask airway was effective in protecting against the risk of aspiration in 3000 elective Cesarean section patients with a minimum fasting period of 8 hr.…”
Section: Discussionmentioning
confidence: 99%